Sinhala Aryans: 424 BC - 1986 AC - De Zoysa, G. H., 1922- (Anuradhapura, Sri Lanka : G.H. De Zoysa, 1986)
A brief history of Sinhaladipa upto the present day with special reference to early period as revealed under the Buddhist era 384 BC and the critical study of the Mahawansa.
Keywords: Sinhala Aryans -- Sri Lanka; History -- Sri Lanka